Mantenimiento y puesta a punto de los bancos didácticos de pruebas neumáticas del laboratorio de neumática de la Universidad Antonio Nariño sede sur. (2024)
The project involved developing a maintenance plan for the pneumatics laboratory at Antonio Nariño University in Bogotá, south campus. The main objective is to ensure the proper functioning and safety of pneumatic equipment and accessories used in the didactic pneumatic test benches for academic practices. To achieve this, various activities were carried out. First, a detailed inspection of each bench was performed to identify potential problems or wear in valves and accessories. A review was conducted to detect leaks, corrosion, wear of joints and seals, among others.